Total Matrix Metalloproteinase-2 and Prostaglandin E2 as Potential Biomarkers in Iraqi AML Patients (Medico Legal Update, 2021)
Acute Myeloid Leukemias (AMLs) are rare but extremely malignant neoplasms that are liable for a bigamount of fatalities associated with cancer. Acute myeloid leukemia (AML) results from accumulation ofabnormal myeloblasts, most commonly in the bone marrow, leading to bone marrow failure and death. Thepresent study was carried out to evaluate MMP-2 and PG E2 in sera and of (50) AML Iraqi patients, In additionto control group involving (50) matched apparently healthy subjects. This study was done in the Nationalcenter of hematology, Department of biology at AL-Mustansiyria University, Baghdad Medical City sinceJanuary 2019 to June 2020. The aim of study was to determine the level of total Matrix Metalloproteinase2 and prostaglandin E2 in patients with AML by ELISA. and study the impact of these parameters on thepathogenesis of disease, also predict the AML and how the parameters correlated with stages and severityof disease and responsiveness to therapy. Conclusion: MMP-2 decreased and elevated of PGE2 in the serumof AML patients .